PEACE JOURNEY: A GAME INSPIRED BY UNO FOR MITIGATING SCHOOL VIOLENCE - da Silva , Ivanise Freitas; da Silva, Aaron Macena; Macena , Raimunda Hermelinda Maia (Seven Editora, 2024)
This study presents the methodological development and validation of the game "Journey of Peace: Building a World without Violence", an educational game based on the dynamics of UNO, aimed at adolescents aged 13 to 17 years. The objective was to create a playful tool capable of stimulating reflections on types of violence, prevention/mitigation strategies and reporting channels, strengthening pro-social behaviors. The development was structured in four phases: integrative literature review, construction of the theoretical framework, prototype development and validation with experts. Professionals from the areas of education, health and design participated in the process, who evaluated the game in terms of educational impact and user experience, based on the ARCS model and Bloom’s Taxonomy. The results indicated positive acceptance, with suggestions incorporated to improve the clarity of the rules, inclusion of representative characters and improvement of interactivity. It is concluded that the "Journey of Peace" game is an innovative and effective tool to sensitize adolescents about violence and encourage preventive attitudes, becoming a promising resource in the school environment. DOI: https://doi.org/10.56238/sevened2024.037-103